Keeping record: the materiality of rulership and administration in early China and Medieval Europe - Armstrong, Abigail S.; Armstrong, Abigail S.; Kuhn, Matthias; Kuhn, Matthias; Peltzer, Jörg; Peltzer, Jörg; Tong, Chun Fung; Tong, Chun Fung; Giele, Enno; Korolkov, Maxim; Kourris, Andrew; Nüllen, Hanna; et al. (Materiale Textkulturen, 2024)
The production and retention of written records was a common and important facet of pre-modern rulership and administration. Much of our understanding of governmental practices and expressions of authority come from the contents of such documents, which have been well studied. Less studied, however, are the records themselves as artefacts. This volume is an attempt to redress this balance by taking a more holistic, material approach to a range of written records. Through a series of case studies, this volume explores questions regarding the material characteristics of various records and their use. It demonstrates that the material features of the records, including the size and shape, the hands that wrote them and the material substrate, can shed new light on the functioning of government and the declarations of power these records asserted. The ten contributions of this volume focus on records from a variety of rulers, political systems and administrations. With four case studies from early China and six from medieval Europe, this volume offers transcultural perspectives to demonstrate how different cultures expressed rulership and administration materially through the use of text-bearing artefacts
This volume results from the online workshop "Keeping Record: The Materiality of Rulership and Administration in the Pre-Modern World", hosted by Heidelberg University on the 24-25 March 2022 - Preface
Gesehen am 03.07.2024
Keywords: Konferenzschrift -- 2022 -- Heidelberg; Geschichte 240 v. Chr.-220; Materialität; Schriftgut; Verwaltung; China; Geschichte 1000-1550; Europa